1996
DOI: 10.1016/s0035-9203(96)90249-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscesses and acute schistosomiasis mansoni: report on 3 cases and experimental study

Abstract: Three children with acute schistosomiasis mansoni developed pyogenic liver abscesses. The abscesses were diagnosed by ultrasonography and confirmed during laparotomy. Staphylococcus aureus were the sole bacteria isolated from the abscesses. An experimental study was carried out in mice to establish whether schistosomiasis is a predisposing cause for pyogenic liver abscesses. Seventeen mice (group 1) were infected with 40 Schistosoma mansoni cercariae (LE strain) and 60 d later inoculated intravenously with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
5
21
0
1
Order By: Relevance
“…Lambertucci and colleagues have described this association in 1990 (Lambertucci et al 1990), and recently Teixeira et al (1996) have confirmed and extended their previous findings.…”
Section: Discussionsupporting
confidence: 60%
“…Lambertucci and colleagues have described this association in 1990 (Lambertucci et al 1990), and recently Teixeira et al (1996) have confirmed and extended their previous findings.…”
Section: Discussionsupporting
confidence: 60%
“…8,12,14,15 It has been reported that acute Schistosoma mansoni, intestinal nematodes, or Toxocara canis infections are risk factors for pyogenic liver abscess and for other staphylococcal infections on both children and adults. [16][17][18] Supporting this hypothesis are preliminary results from our laboratory, which indicate that the production of interleukin-4 and -10 by CD3…”
Section: Introductionmentioning
confidence: 75%
“…Forty thousand colony forming units (CFU), as determined by nephelometer, were injected into the tail vein, according to the method previously described. 10 The bacterial infection was done after 60 days (acute phase) and 120 days (chronic phase) of being infected with cercariae, and 30 days after the treatment of schistosomiasis.…”
Section: Methodsmentioning
confidence: 99%
“…5 Hepatic hydatid cysts (Ecchinococcus granulosus) also become secondarily infected. 6 In addition, migrating Ascaris lumbricoides 7,8 and, more recently, acute schistosomiasis [9][10][11] have been implicated as predisposing factors in the genesis of pyogenic liver abscess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation